The medieval Salento : art and identity in Southern Italy - Safran, Linda (Middle Ages series., 2014)
The Medieval Salento explores the visual and material culture of people who lived and died in this region between the ninth and fifteenth centuries, showing the ways Jews, Orthodox Christians, and Roman-rite Christians used images, artifacts, and texts in Hebrew, Greek, and Latin to construct both independent and intersecting identities.